A feasibility study on the extension of the online public access catalog of the University of the Philippines Diliman Main Library to mobile phone users through SMS - Amparo, Jennifer C.; Angeles, Chito N. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
The University of the Philippines Diliman Main Library, from hereon referred to as the University Library, has always been known for being one of the pioneers in automation. It is one of the first to go on the Web to give the public access to its extensive collection thru its Online Public Access Catalog (OPAC).The author of this study believes the University Library will continue to maintain leadership in information technology in the academe through a proposal to add a Short Messaging Service (SMS) to its existing infrastructure, given the wide use of mobile phones within the campus.
The question is: is it possible to provide library users information similar to that provided by the OPAC by through SMS? The first step is to determine the acceptability of the proposal to a sample of library book users in the UP Diliman community. The second is to find out the possibility of executing the proposal, given certain areas of consideration.
The findings at the end of the study reveal more than was expected by the author. The positive response to the proposal from the library users/mobile phone users surveyed was not surprising. What was encouraging was the discovery of the author, in the course of the study, that the University Library is already engaged in upgrading its library automation system. The library is in fact, embarking on a new phase that would further strengthen its position as a technological pioneer and emphasize its responsibility of extending more service and convenience to its select clientele.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) Main Library; Online library catalogs -- Remote access. -- Philippines